Tecnologias para produção de mudas de espinheira-santa: propagação vegetativa por estacas caulinares - Alves, Lucas Ferenzini [UNESP] (2015)
Espinheira-Santa is a medicine plant and its therapeutic properties is proven scientifically with features to several treatments, such as gastric, diuretic, ulcers, healing skin conditions and painkillers effect. This species rooting is difficult; consequently its vegetative propagation becomes a challenge. The species is considered difficult to rooting, making it difficult to vegetative propagation. This study aimed to generate technologies for production of espinheira-santa seedlings. It was conducted four experiments from March 2013 to July 2014, consisting of effects such as cuttings, plant growth regulators, prepared homeopathic and seasonality. All of that was based on stem stem cutting. This experiment was conducted in a vegetation house covered with shade cloth and intermittent mist for four months. The stem cuttings were collected from the access, which belonging to Medicinal Garden of Horticulture Department in Lageado Experimental Farm at Faculdade de CiênciasAgronômicas - Unesp - Botucatu Campus, SP. In the stem cutting types experiment, it was assessed three different withdrawing branch position to produce the stem cuttings (apical, median and basal), at that time it was not observed significant differences in the characteristics accessed. In the regulators trial was beholden two hormones types: synthetic and natural, in different concentrations: 0mg.L-1 (distilled water evidence), 250mg.L-1, 500mg.L-1, 750mg.L-1, 1000mg.L-1 of indolebutyric acid (IBA) to synthetic treatment, and 0% (evidence), 25%, 50%, 75% and 100% of aqueous extract of nutsedge bulb (Cyperus rotundus L.), whereupon the synthetic regulator treatment was extremely toxic, causing the total mortality of all stem cuttings during the four processing. The natural regulator contributes to the stem cuttings survival and helped in their rooting percentage, though the concentrations above 50% ...